2016
DOI: 10.1016/j.molimm.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane protein 88 attenuates liver fibrosis by promoting apoptosis and reversion of activated hepatic stellate cells

Abstract: Transmembrane protein 88 (Tmem88) is a crucial inhibitor for Wnt/β-catenin pathway in the development of myocardial cells. Due to the important role of β-catenin in the activation and proliferation of hepatic stellate cells (HSCs), it is necessary to investigate the function of Tmem88 in HSCs. In this study, we found that Tmem88 expression was decreased in the human liver fibrotic tissues, primary HSCs from fibrotic mice and activated HSC-T6 cells. Functionally, Tmem88 could inhibit HSCs activation and prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Primary HSCs were isolated from mice as previously described 28 . Liver of mice was digested with Collagenase IV (Sigma-Aldrich, St. Louis, USA) and Pronase E (Sigma-Aldrich, St. Louis, USA) dissolved in PB buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Primary HSCs were isolated from mice as previously described 28 . Liver of mice was digested with Collagenase IV (Sigma-Aldrich, St. Louis, USA) and Pronase E (Sigma-Aldrich, St. Louis, USA) dissolved in PB buffer.…”
Section: Methodsmentioning
confidence: 99%
“…TMEM88 expression is decreased in the human liver fibrotic tissues. In vitro assays prove that TMEM88 inhibits activation and proliferation of hepatic stellate cells (HSCs) by blocking Wnt/β-catenin pathway, and promotes the activated HSCs apoptosis by initiating Bcl-2/Bax/Caspase3 pathway [14]. TMEM88 was also found to be downregulated in renal fibrotic tissues and TGF-β1-treated HK2 cells.…”
Section: Discussionmentioning
confidence: 98%
“…attenuates liver fibrosis via regulating Wnt/β-catenin and Bcl-2/Bax/Caspase3 signaling pathways [14]. Zhao et al [15] reported that TMEM88 inhibits hyper-proliferation and migration of fibroblasts and suppresses excess ECM deposition in TGF-β1-stimulated keloid-derived fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…TMEM88 inhibits Wnt/β-Catenin signaling through interaction with the Wnt pathway factor Dishevelled ( DVLS ) 14 . Therefore, the hypermethylation of the TMEM88 gene may inhibit its function as a negative modulator of Wnt/β-Catenin signaling, which results in the constitutive activation of this signal pathway in NSCLC 30 . This may explain why the hypermethylation of TMEM88 in NSCLC is associated with an unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%